Effect of barley sowing density on the integrated weed management of lolium rigidum (Annual ryegrass) in mediterranean dryland: A modeling approach - D'amico, Edith Maria Belen (2021)
Population models are particularly helpful for understanding long-term changes in the weed dynamics associated with integrated weed management (IWM) strategies. IWM practices for controlling L. rigidum are of high importance, mainly due to its widespread resistance that precludes chemical control as a single management method. The objective of this contribution is to simulate different IWM scenarios with special emphasis on the impact of different levels of barley sowing densities on L. rigidum control. To this effect, a weed-crop population model for both L. rigidum and barley life cycles was developed. Our results point out: (i) the necessity of achieving high control efficiencies (>99%), (ii) that the increase of twice the standard sowing density of barley resulted in a reduction of 23.7% of the weed density, (iii) non-herbicide-based individual methods, such as delayed sowing and weed seed removal at harvest, proved to be inefficient for reducing drastically weed population, (iv) the implementation of at least three control tactics (seed removal, delay sowing and herbicides) is required for weed infestation eradication independently of the sowing rate, and (v) the effect of an increase in the sowing density is diluted as a more demanding weed control is reached. Future research should aim to disentangle the effect of different weed resistance levels on L. rigidum population dynamics and the required efficiencies for more sustainable IWM programs.